Pembuatan Media Promosi Berbasis Company Profile Video dengan Aplikasi Sony Vegas Pro 13 Pada Tidar Property Group Kota Malang - Cahyanti, Meyrinda Putri; Wardani, Rr. Tri Istining (Universitas Pahlawan Tuanku Tambusai, 2024)
The main purpose of this study is to create a corporate company profile video for promotional media. Then the researcher uses EPIC Model formula to calculate the effectiveness of the video design. Then the admin of Tidar Property Group upload it on Instagram social media of @TidarPropertygroup. The research location was at Tidar Property Group with a total number of respondents was 21, 1 business owner, 1 employee, 2 marketing professionals, 2 multimedia professionals, and 15 potential customers. This research was an action research, this study used data collection tehniques such as observation, interview, questionnaires, and documentation. The researcher conducted stages starting with planning, acting, observing, and reflecting. This research shows that the average EPIC Rating score is 4.25 out of 5. This score indicates that the company profile videos belong to the highly effective category. According to this study, company profile videos is suitable as an promotional media and can definitely increase brand awareness for potential customers. The author suggests for companies to use company profile videos as promotional media. For future researchers, it is hoped that the company profile video development will be better in terms of shooting techniques, tools used, and editing applications